Alternativno podpiranje in dvigovanje obstoječe jeklene konstrukcije starega poškodovanega mostu čez Savo v Brežicah za potrebe sanacije - Hladnik, Leon (Gradbeni vestnik, 2021)
The article describes the implementation of alternative support and lifting of the existing steel structure of the demanded bridge over the Sava River for the needs of rehabilitation. The lifting relieved the damaged lower beams of trusses, allowing them to be gradually replaced. The design of the alternative support structure without support in the river bed and the phasing of the support, lifting and rehabilitation are described. The main results of monitoring during support and lifting and the lowering performed after the completed rehabilitation are given.
Keywords: alternative support; damage elements; dotrajani elementi; dvigovanje; jeklena konstrukcija; lifting; monitoring; mostovi; rehabilitation; sanacija; steel construction